Earth system processes and disaster management - Ravindra, Rasik; Sinha, Rajiv (Society of Earth Scientists Series,, 2013)
One of the fundamental goals of earth system science research is to adopt a more holistic view of the earth as a 'system' comprising different domains. The Society of Earth Scientists has brought out this multidisciplinary publication to emphasize the need of an integrated approach to understand the Earth system. It focuses on natural disasters and, in particular, on climate change and its effects in Asia and understanding the significance of these developments within the context of the paleo-climatic record. The later sections of the book then focus on other types of natural disasters as well as those induced by human interaction with our environment.